(untitled) (Acta Entomologica Serbica, 2019)
A checklist for Iranian Criocerinae Latreille (Coleoptera: Chrysomelidae) is proposed. Based on a literature review, a total of 13 species within four genera, Crioceris Geoffroy (five species), Lilioceris Reitter (four species), Lema Fabricius (one species) and Oulema Des Gozis (three species), are given. Among the listed species, Lema (Lema) cyanella Linnaeus, 1758 is a new record for the fauna of Iran.